(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Endothelin-1 plays a role as a vasoconstrictor and also inhibits the expression of adiponectin in obesity. The Lys198Asn polymorphism of the endothelin-1 gene will increase the level of endothelin-1 plasma and increase the risk factor of obesity. Objective: In this study, we investigated the relationship between Lys198Asn polymorphism of endothelin-1 gene and endothelin-1 plasma level among individuals with obesity in Javanese population. Method: This study was conducted on 61 obese subjects and 65 control subjects. All subjects were measured for anthropometrics and endothelin-1 plasma level by ELISA (Enzyme-linked Immune Sorbent Assay). The polymorphism of Lys198Asn of ET-1 (Endothelin-1) was screened by using PCRRFLP (Polymerase Chain Reaction- Restriction Fragment Length Polymorphism). Results: TT genotype was a risk factor of obesity (OR 5.344 CI=95% 1.77-16.16) compared with GG genotype. Levels of endothelin-1 plasma were higher in obese subjects than that of control subjects (p=0.013), with TT genotype having the highest endothelin-1 plasma level (p<0.001). Conclusion: The Lys198Asn polymorphism of endothelin-1 gene plays a role in increasing endothelin-1 plasma levels and is risk factors of obesity. Bangladesh Journal of Medical Science Vol.18(1) 2019 p.46-49